View of the Growing Progress of the Iraqi Novel - Maysaa Nabeel Abdulhameed; Ali Abd Alrahman Fattah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Concerning the Iraqi modern novel, it first appeared and grew in an incomplete structure till it reached a satisfactory maturity and perfection during the sixties and seventies of the previous century and the beginning of the twenty first century. The Iraqi modern novel added to its perfection some tasks through which most Iraqi novelists have endeavored to express the agonies of their people and country. They also concentrated on the great loss and waste that inflicted Iraq following the great latest war of 2003. The Iraqi modern novelists undertook all those missions and worked on combining in the structural frameworks of their novels imagination and reality mainly to reach the tightest narrative style. However, if this style is not realistic, it depicts realism by imitating it.